AI-Based tool to support emotional diagnosis in children through drawings (Innovation & Development in Engineering and Applied Science, 2026)
This article presents the development of a technological tool based on artificial intelligence for the analysis of children's drawings, in order to support therapists in the detection of emotions in children aged 5 to 7 years. The solution is implemented through a mobile application developed in MIT App Inventor, which captures images of the drawings and sends them to a Flask server hosted on a Raspberry Pi for processing. The tool uses the HSV color model to analyze the colors used by children and, through an artificial intelligence API, generate preliminary diagnoses about their emotional state. The system is designed to optimize the early detection of emotional patterns, facilitating the work of therapists and parents in understanding children's psychological well-being. This project represents a contribution to the field of multimedia communication and data processing applied to children's mental health.
Keywords: Artificial intelligence; Dibujos infantiles; Detección de emociones